Effect of high ligation on survival of patients undergoing surgery for primary colorectal cancer and synchronous liver metastases. Issue 3 (3rd April 2020) - Matsui, S.; Okabayashi, K.; Hasegawa, H.; Tsuruta, M.; Shigeta, K.; Ishida, T.; Yamada, T.; Kondo, T.; Yamauchi, S.; Sugihara, K.; Kitagawa, Y.
Abstract : Background: Although R0 surgery is recommended for stage IV colorectal cancer, the degree of required lymphadenectomy has not been established. The aim of this study was to investigate the prognostic impact of high ligation (HL) of the feeding artery and the number of retrieved lymph nodes after R0 surgery for colorectal cancer and synchronous colorectal cancer liver metastasis (CRLM). Methods: This was a multi‐institutional retrospective analysis of patients with colorectal cancer and synchronous CRLM who had R0 surgery between January 1997 and December 2007. Clinical and pathological features were compared in patients who underwent HL and those who had a low ligation (LL). Kaplan–Meier analysis was performed to estimate the effect of HL on overall survival (OS). The impact of several risk factors on survival was analysed using the Cox proportional hazards model. Results: Of 549 patients, 409 (74·5 per cent) had HL. Median follow‐up was 51·4 months. HL significantly improved the 5‐year OS rate (58·2 per cent versus 49·3 per cent for LL; P = 0·017). Multivariable analysis revealed HL to be a significant prognostic factor compared with LL (5‐year mortality: hazard ratio (HR) 0·68, 95 per cent c.i. 0·51 to 0·90; P = 0·007). In subgroup analysis, the positive effect of HL on OS was greatest in patients with lymph node metastasis. Conclusion: HL of the feeding artery was associated with improved OS in patients with colorectal cancer and synchronous CRLM after R0 surgery. Abstract : Although R0 surgery is recommended for stage IV colorectal cancer, the degree of lymphadenectomy required has not been established. A multi‐institutional retrospective analysis was done of patients with colorectal cancer and synchronous hepatic metastases who were treated with R0 surgery. More aggressive lymphadenectomy could improve the overall survival of these patients. High ligation improves survival. Abstract : Antecedentes: Aunque se recomienda una cirugía R0 para el cáncer colorrectal ( colorectal cancer, CRC) en estadio IV, no se ha establecido el grado de linfadenectomía requerida. El objetivo de este estudio fue investigar el impacto pronóstico de la ligadura alta ( high ligation, HL) de la arteria que irriga el tumor y el número de ganglios linfáticos ( lymph nodes, LN) identificados después de cirugía R0 en pacientes con cáncer colorrectal y metástasis hepáticas sincrónicas ( colorectal cancer liver metastasis, CRLM). Métodos: En este estudio se realizó un análisis retrospectivo multicéntrico de pacientes con CRC y CRLM sincrónicas en los que se realizó una cirugía R0 desde enero de 1997 hasta diciembre de 2007. Se compararon las características clínicas y patológicas entre los pacientes a los que, durante la cirugía R0, se practicó una HL frente a los que no se practicó esta técnica. El análisis de Kaplan‐Meier se realizó para estimar el efecto de la HL en la supervivencia global ( overall survival, OS). El impacto de varios factores de riesgo sobre la supervivencia se analizó utilizando el modelo de Cox de riesgo proporcional. Resultados: Sobre un total de 549 pacientes, se realizó una HL en 409 (74, 5%), y el período de seguimiento medio en esta cohorte fue de 51, 4 meses. La HL mejoró significativamente la tasa de OS a los 5 años (HL 37, 7% versus no HL 27, 1%, P = 0, 02). El análisis multivariable mostró que la HL era un factor pronóstico significativo en comparación con la no realización de una HL (cociente de riesgos instantáneos, hazard ratio, HR de muerte a 5 años = 0, 68 (i.c. del 95% 0, 51‐0, 90), P < 0, 01)). En el análisis de subgrupos, el efecto positivo de la HL sobre la OS fue mayor en pacientes con metástasis ganglionares. Conclusión: La ligadura alta de la arteria que irriga el tumor se asoció con una mejor OS en pacientes con CRC y CRLM sincrónicas después de una cirugía R0.